Surgery for anomalous aortic origin of coronary arteries: a multicentre study from the European Congenital Heart Surgeons Association. (20th March 2019) - Padalino, Massimo A; Franchetti, Nicola; Hazekamp, Mark; Sojak, Vladimir; Carrel, Thierry; Frigiola, Alessandro; Lo Rito, Mauro; Horer, Jurgen; Roussin, Regine; Cleuziou, Julie; Meyns, Bart; Fragata, Jose; et al.
Abstract: OBJECTIVES: We sought to describe early and late outcomes in a large surgical series of patients with anomalous aortic origin of coronary arteries. METHODS: We performed a retrospective multicentre study including surgical patients with anomalous aortic origin of coronary arteries since 1991. Patients with isolated high coronary takeoff and associated major congenital heart disease were excluded. RESULTS: We collected 156 surgical patients (median age 39.5 years, interquartile range 15–53) affected by anomalous right (67.9%), anomalous left (22.4%) and other anatomical abnormalities (9.6%). An interarterial course occurred in 86.5%, an intramural course in 62.8% and symptoms in 85.9%. The operations included coronary unroofing (56.4%), reimplantation (19.2%), coronary bypass graft (15.4%) and other (9.0%). Two patients with preoperative cardiac failure died postoperatively (1.3%). All survivors were discharged home in good clinical condition. At a median follow-up of 2 years (interquartile range 1–5, 88.5% complete), there were 3 deaths (2.2%), 9 reinterventions in 8 patients (5 interventional, 3 surgical); 91.2% are in New York Heart Association functional class ≤ II, but symptoms persisted in 14.2%; 48.1% of them returned to sport activity. On Kaplan–Meier analysis, event-free survival at follow-up was 74.6%. Morbidity was not significantly different among age classes, anatomical variants and types of surgical procedures. Furthermore, return to sport activity was significantly higher in younger patients who participated in sports preoperatively. CONCLUSIONS: Surgical repair of anomalous aortic origin of coronary arteries is effective and has few complications. Unroofing and coronary reimplantation are safe and are the most common procedures. The occurrence of late adverse events is not negligible, and long-term surveillance is mandatory. Most young athletes can return to an unrestrained lifestyle.